Sport in business studies: a state-of-the-art literature review. Issue 5 (6th September 2018) - Laurell, Christofer; Soderman, Sten
Abstract : Purpose: The purpose of this paper is to provide a systematic review of articles on sport published in leading business studies journals within marketing, organisational studies and strategy. Design/methodology/approach: Based on a review of 38 identified articles within the subfields of marketing, strategy and organisation studies published between 2000 and 2015, the articles' topical, theoretical and methodological orientation within the studied subfields were analysed followed by a cross-subfield analysis. Findings: The authors identify considerable differences in topical, theoretical and methodological orientation among the studied subfields' associated articles. Overall, the authors also find that articles across all subfields tend to be focussed on contributing to mature theory, even though the subfield of marketing in particular exhibits contributions to nascent theory in contrast to organisation studies and strategy. Originality/value: This paper contributes by illustrating the current state of research that is devoted or related to the phenomenon of sport within three subfields in business studies. Furthermore, the authors discuss the role played by leading business studies journals vis-à-vis sport sector-specific journals and offer avenues for future research.